Strategies for Correcting Misinformation about Vaccination and Increasing Coverage: Relevance for Health Education - Opoku, Albert; Adjei, Thomas A. Asafo; Owusu, Nicholas Amoah (British Journal of Healthcare and Medical Research, 2025)
Vaccination continues to be one of the most important mechanisms for the prevention of diseases in public health worldwide. The introduction of vaccination programmes has resulted in an increase in life expectancy in the world, which is one of humanity’s greatest achievements. According to the WHO, vaccination could prevent between 2 and 3 million deaths per year worldwide. That notwithstanding, misinformation about vaccines is on the ascendency, leading to vaccination hesitancy globally. This review article aims to correct the misinformation leading to vaccination hesitancy and suggest strategies to improve vaccination in various countries. The information in this article could then be used for public health education on the need to accept vaccines to prevent diseases.